Batch and column studies on methylene blue using activated carbon/Al2O3 nano-composite and its impregnated calcium alginate beads (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Activated carbon/Al2O3 nano-composite (ANC) was synthesized by simple pyrolysis after incorporating the aluminium acetate precursor in activated carbon (AC) matrix. The as-synthesized composite was characterized by FT-IR, XRD, BET isotherm, SEM, EDX, and TEM. The size of Al2O3 nanoparticles in carbon matrix was found to be in the range of 10-35 nm. Adsorption characteristics of nano-composite was evaluated using methylene blue dye (MB) by batch and column studies. In batch process, the effect of concentration, temperature and pH were investigated. Batch adsorption study was interpreted with Langmuir, Freundlich, Temkin and Dubinin-Radushkevich (D-R) isotherms. Results showed that adsorption follows Freudlich isotherm model with an adsorption capacity of 116 mg/g at pH 7 at 30 Â°C and it increases with increase in pH. Kinetic data indicated that the adsorption of dye follows pseudo-second order kinetics model. The negative value of Î”G indicates the spontaneous nature of the adsorption process. For column study the nano-composite was fabricated into Calcium alginate beads (CAB). The performance of CAB was studied with different influent concentrations of MB, pH and bed depth and the results have been interpreted using Thomas and BDST models. The column shows an adsorption capacity of 285.57 mg/g of CAB at pH 7 with bed height of 10 cm and best fitted to BDST model. These outcomes indicate the capability of carbon/Al2O3 nano-composite for dye removal.